Zinc Oxide Nanoparticles Synthesis Methods and its Effect on Morphology: A Review - Droepenu, Eric Kwabena; Wee, Boon Siong; Chin, Suk Fun; Kok, Kuan Ying; Muhammad Firdaus, Maligan (Biointerface Research, 2022)
Zinc oxide is an important material with numerous applications due to its unique properties. Due to their thermal and chemical stability are used in wide applications such as LEDs, sensors, catalysts, and photodetectors. Different chemical, physical, and biological methods have been adopted to achieve the intended result, as enumerated in many pieces of literature. Therefore, selecting an efficient synthesis process is essential, which is a key factor that significantly influences the efficacy of the synthesized nanocrystalline materials. The chemical synthesis of nanoparticles (NPs) via hydrothermal, solvothermal, and sol-gel routes is considered effective as high-quality crystalline structures are produced. Control of parameters of processes yields excellent morphological features of the synthesized samples. This review explored the different parameters of processes and their effect on the morphology of ZnO nanostructures via hydrothermal, solvothermal, and sol-gel techniques. Finally, some ZnO nanocomposites molecules are reviewed as per the dopant used and its effect on the sample compound synthesized.